Skrining Penyakit Tidak Menular (PTM) di Wilayah Kerja Puskesmas Sukarami Palembang - Sri Indaryati; Maria Tarisia Rini; Keristina Ajul; Novita Anggarini; Lusia Sudarmi (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Non-Communicable Disease (NCD) Screening is an early effort to identify NCD risk factors in individuals or groups through the Integrated Development Post (Posbindu) NCD. NCDs consist of Hypertension, Diabetes Mellitus, Cervical and Breast Cancer, and Chronic Obstructive Pulmonary Disease. NCDs are increasing and are the main cause of death of the population. In 2030, it is targeted that at least the number of premature deaths due to NCDs can be prevented through the SDGs program by 25%. The Faculty of Health Sciences (Fikes) of Musi Charitas Catholic University (UKMC) is part of the Sukarami Health Center Working Area which has 396 students in the 2024/2025 academic year. Fikes finds out whether or not there are NCD risk data factors in students. Lecturers and Officers of the Sukarami Health Center are actively conducting NCD screening using the Posbindu activity method, namely 5 Tables (Registration, Interview, Measurement, Examination and Counseling/Education). The target of all UKMC Fikes students who are studying on campus is 287 (72.47%). The activities carried out were measuring Body Weight (BB), Height (BB), determining Body Mass Index (BMI). Implementation of procedures in accordance with the guidelines set by the Indonesian National Nurses Association (PPNI). Results: The target achievement was 245 (85.37%) of the original target of 287. Analysis results 1) Students who have a BMI > 25 are 72 (29.39%) students; have a waist circumference > 80 (women) and > 90 (men) are 62 (25%) students. Blood pressure > 130/90 mmHg is owned by 6 (2.45%) students, while random blood sugar > 180 mg/dl is owned by 1 (0.41%) student. Suggestions or Follow-up Action Plans: All students are screened periodically and PTM control is carried out.